2020
DOI: 10.1186/s12974-020-01888-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation is associated with infiltration of T cells in Lewy body disease and α-synuclein transgenic models

Abstract: Background: α-Synuclein (α-syn) is a pre-synaptic protein which progressively accumulates in neuronal and nonneuronal cells in neurodegenerative diseases such as Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy. Recent evidence suggests that aberrant immune activation may be involved in neurodegeneration in PD/DLB. While previous studies have often focused on the microglial responses, less is known about the role of the peripheral immune system in these disorders. Methods:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 95 publications
8
68
0
Order By: Relevance
“…The regional distribution of the cells in the brain may account for why T cells were more effective in reducing nigral pathology, but not striatal or cortical pathology. Although we could not determine regional differences in T cell infiltration in the brain, our findings of CD3 + and CD4 + T cells in the brain align well with a growing body of evidence that T cells invade the central nervous system in neurodegenerative conditions [29,63,64].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The regional distribution of the cells in the brain may account for why T cells were more effective in reducing nigral pathology, but not striatal or cortical pathology. Although we could not determine regional differences in T cell infiltration in the brain, our findings of CD3 + and CD4 + T cells in the brain align well with a growing body of evidence that T cells invade the central nervous system in neurodegenerative conditions [29,63,64].…”
Section: Discussionsupporting
confidence: 83%
“…T lymphocytes are altered and infiltrate the brain in PD [19][20][21][22][23][24][25][26] and it has been reported that autoreactive T lymphocytes directed against α-syn are present in PD patients [27] decades prior to motor PD [28]. Recruitment of CD4+ T cells to the brain occurs in models of a-syn overexpression [29]. In PD models, T cell function has been linked to α-syn pathobiology [30][31][32] and to the death of dopamine neurons [8,33].…”
Section: Introductionmentioning
confidence: 99%
“…Infiltration of T lymphocytes in the brain parenchyma has also been observed in other synucleinopathies. In particular, CD4 + but not CD8 + or B lymphocytes were found to be increased in the frontal cortex and hippocampus of cases with dementia with Lewy bodies (DLB) compared to controls at postmortem [35].…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of T lymphocytes in the brain parenchyma has also been observed in other synucleinopathies. In particular, CD4 + but not CD8 + or B lymphocytes were found to be increased in the frontal cortex and hippocampus of cases with dementia with Lewy bodies (DLB) compared to controls at postmortem [ 35 ]. A second recent study in DLB cases showed increased T lymphocyte infiltration in both the grey and white matter of the middle temporal gyrus, in the absence of prominent microglial activation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of the peripheral immune system in PD-related neuroinflammation has not yet been entirely elucidated, infiltrating CD4 + and CD8 + T lymphocytes have been suggested to contribute to neurodegeneration 65 . CD3 + T cells, which have been found in close proximity to glial cells in brains of DLB patients and α-synuclein transgenic mice, have been suggested to participate in activation of glial cells 66 . In vitro studies suggested that CD4 + /CD25 − effector T cells promote microglial activation and contribute to neurodegeneration while CD4 + / CD25 + Tregs might be inhibiting microgliosis 67 .…”
Section: Discussionmentioning
confidence: 99%